The Effect of Intentional Nursing Rounds Based on the Care Model on Patients' Perceived Nursing Quality and their Satisfaction with Nursing Services - Nayeon Shin; Jummi Park (Elsevier, 2018)
Purpose: This study examined the effects of intentional nursing rounds based on the care model on patients' perceived nursing quality and their satisfaction with nursing services. Methods: The study design was a nonequivalent control group pretest-posttest design. The participants were assigned to the intervention group or the control group in two orthopedic wards of a teaching hospital. A total of 9 rounds (at 7 AM, 9 AM, 12 PM, 3 PM, 5 PM, 8 PM, 10 PM, 2 AM, and 5 AM) were performed every 2 or 3 hours to the experimental group. The intentional nursing rounding intervention was developed through a theoretical development program involving six basic principles which are maintaining belief, knowing, being with, doing for, enabling, and patients' wellness. To evaluate the effects of intentional nursing rounds, data were collected through the Perception of Quality Nursing Care Scale and the Patients' Satisfaction with Nursing Care Quality Questionnaire. Results: The participants were 70 patients (experimental group) and 75 patients (control group). Results of difference-in-difference analysis confirmed that the patient-perceived nursing quality level from the experimental group was 0.85 points (out of 5.00) higher (p = .041) and the satisfaction with nursing services level was 8.28 points (out of 110.00) higher (p < .001) than the control group. Conclusions: These results proposed that intentional nursing rounds based on the care model were effective in improving perception of quality nursing care and patients' satisfaction with nursing care. Structured patient-oriented intentional nursing rounds based on the care model are expected to expand to a variety of clinical settings further. Keywords: nursing care, nursing services, hospital, patient satisfaction, quality of health care